Aspekt und Aktionsart : Grundriss und Fallstudie an altassyrischen Texten. - Schilling, Guido W. G. (Wiesbaden : Harrassowitz Verlag, 2019)
The monograph by Guido W.G. Schilling includes both an introduction to the grammatical category of aspect and a detailed case study of its function in Old Assyrian. The first part of the study presents the history of science and the current state of aspect research. Explained and conceptually distinguished among grammatical categories are not only the perfective and imperfective aspects, but also the perfect and progressive aspects. In the domain of lexical aspect, actionality, verbal character, and situation types are elucidated. Special attention is given to grammatical categories interacting with aspect, including not only tense but also transitivity and semantic relation. A separate chapter on the research method discusses issues related to data collection and the procedure of morpheme glossing in corpora of ancient languages. The case study of Old Assyrian texts provides a catalog of readings of grammatical and lexical aspect categories of verbs and the significance of semantic relations for the grammar of the Akkadian verbal system. Through systematic language typological analysis, it is demonstrated that Akkadian syntactically offers an aspect system, but that the entire paradigm and lexicon structure can only be conceptually grasped on a semantic level.
JSTOR
Keywords: Akkadian language -- Aspect; Akkadien (Langue) -- Aspect; FOREIGN LANGUAGE STUDY / Ancient Languages